Magnetization transfer imaging of normal and abnormal testis: preliminary results - Tsili, Athina C.; Ntorkou, Alexandra; Baltogiannis, Dimitrios; Sylakos, Anastasios; Stavrou, Sotirios; Astrakas, Loukas G.; Maliakas, Vasilios; Sofikitis, Nikolaos; Argyropoulou, Maria I. (European radiology, 2016)
Objectives The aim was to determine the magnetization transfer ratio (MTR) of normal testes, possible variations with age and to assess the feasibility of MTR in characterizing various testicular lesions. Methods Eighty-six men were included. A three-dimensional gradient-echo MT sequence was performed, with/without an on-resonance binomial prepulse. MTR was calculated as: (SIo-SIm)/(SIo) × 100 %, where SIm and SIo refers to signal intensities with and without the saturation pulse, respectively. Subjects were classified as: group 1, 20-39 years; group 2, 40-65 years; and group 3, older than 65 years of age. Analysis of variance (ANOVA) followed by the least significant difference test was used to assess variations of MTR with age. Comparison between the MTR of normal testis, malignant and benign testicular lesions was performed using independent-samples t testing. Results ANOVA revealed differences of MTR between age groups ( F = 7.51, P = 0.001). Significant differences between groups 1, 2 ( P = 0.011) and 1, 3 ( P < 0.001) were found, but not between 2, 3 ( P = 0.082). The MTR (in percent) of testicular carcinomas was 55.0 ± 3.2, significantly higher than that of benign lesions (50.3 ± 4.0, P = 0.02) and of normal testes (47.4 ± 2.2, P < 0.001). Conclusions MTR of normal testes decreases with age. MTR might be helpful in the diagnostic work-up of testicular lesions. Key Points • MTR of normal testes shows age-related changes. • Testicular carcinomas have high MTR values. • MTR may be useful in the diagnostic work-up of testicular lesions.